Predictors of Human Papillomavirus Seropositivity in Appalachian Women Aged 18 to 26 Years. Issue 9 (29th September 2021) - Ruffin, Mack T.; Hade, Erinn M.; Fahey, Patrick; Christian, Lisa M.; Paskett, Electra D.; Harper, Diane M.
Abstract : Appalachian women 18 to 26 years old have high baseline seropositivity rates for at least 1 of the 4 human papillomavirus vaccine–related types, but low vaccine-relevant type infections. Supplemental digital content is available in the text. Abstract : Background: Key informants of the Appalachian community questioned whether their unique environmental stressors would alter their immune response to human papillomavirus (HPV) infections. The primary aim of this study is to determine predictors of HPV seroprevalence to at least 1 of the 4 vaccine-related HPV types before vaccination using a psychoneuroimmunologic model in Appalachian women. Method: Women aged 18 to 26 years (n = 185) who had not received HPV vaccination provided cervical HPV DNA and blood samples. Human papillomavirus DNA was identified through Hybrid Capture 2 assay and then genotyped for HPV types 6, 11, 16, and 18 by Roche Linear Array. Competitive Luminex Immunoassay measured the type-specific antibodies to HPV types 6, 11, 16, and 18 in milli-Merck units per milliliter. Nine psychoneuroimmunology scales measuring attributes of stress were self-completed. Results: Human papillomavirus DNA was detected in 50% (92/183) of participants, with only 14% (26/183) positive for HPV-6/11/16/18 DNA. Seropositivity for at least one anti–HPV-6/11/16 or 18, on the other hand, was present in 35% (64/183) of women, with only 10% (19/183) concomitantly infected and seropositive for the vaccine-related types. The Perceived Stress Scale was not a strong predictor of HPV seropositivity. Conclusions: Both HPV infection and vaccine-related HPV type seropositivity is common among Appalachian women aged 18 to 26 years. The anticipated effect of environmental stressors on HPV seropositivity was not seen when multiple predictors were considered.